Quantitative effects of environmental variation on stomatal anatomy and gas exchange in a grass model - Nunes, Tiago D. G.; Slawinska, Magdalena W.; Lindner, Heike; Raissig, Michael Thomas (Quantitative plant biology, 2022)
, - - Stomata are cellular pores on the leaf epidermis that allow plants to regulate carbon assimilation and water loss. Stomata integrate environmental signals to regulate pore apertures and adapt gas exchange to fluctuating conditions. Here, we quantified intraspecific plasticity of stomatal gas exchange and anatomy in response to seasonal variation in Brachypodium distachyon. Over the course of 2 years, we (a) used infrared gas analysis to assess light response kinetics of 120 Bd21-3 wild-type individuals in an environmentally fluctuating greenhouse and (b) microscopically determined the seasonal variability of stomatal anatomy in a subset of these plants. We observed systemic environmental effects on gas exchange measurements and remarkable intraspecific plasticity of stomatal anatomical traits. To reliably link anatomical variation to gas exchange, we adjusted anatomical g - smax calculations for grass stomatal morphology. We propose that systemic effects and variability in stomatal anatomy should be accounted for in long-term gas exchange studies.
Gesehen am 24.06.2024